The dynamics of brand loyalty across a consumer’s lifetime: an application to the Portuguese fashion market - Nunes, Rita Mourato Catela (2015)
This project studies the Portuguese female fashion market. We intend to determine patterns of consumer brand loyalty across brands and ages. By interviewing 8 young adults and surveying 125 teens and 87 adults, we found that brands’ segmentation by usage per age segment is related with differentiation in brand loyalty and peer pressure. We also found that teens have higher attitudinal brand loyalty while adults have higher behavioral loyalty. Moreover, brand loyalty in teens is more susceptible to peer pressure. The results imply that customer relationship management strategies should be differentiated according to age segment. We also derive marketing implications with a focus on each brand’s loyalty profile.